Enhanced electromechanical properties in low-temperature gadolinium-doped ceria composites with low-dimensional carbon allotropes. Issue 8 (1st February 2022) - Han, Jin Kyu; Kabir, Ahsanul; Tinti, Victor Buratto; Santucci, Simone; Song, Da Som; Kim, So Young; Song, Wooseok; Kim, Eunyoung; Bu, Sang Don; Kern, Frank; de Florio, Daniel Zanetti; Esposito, Vincenzo
Abstract : A new functional carbon–metal oxide hybrid is designed and fabricated by field-assisted sintering—the hybrid material results in enhanced electro-chemo-mechanical properties with high crystallinity, facile fabrication method, and cost-efficiency. Abstract : We couple the spark plasma sintering (SPS) technique with the ball mill process to fabricate a new electro-chemo-mechanical functional carbon–metal oxide hybrid material. Graphene oxide (GO) or carbon nanotubes (CNT) carbon allotropes are mechanically mixed with gadolinium-doped ceria (CGO). SPS allows consolidating dense carbon–metal oxide hybrids with uniform morphology and high crystallinity. The carbon allotropes and SPS lead to highly reduced CGO. The metal oxide presents a chemically tuned grain boundary with highly oxygen defect concentration at the near-grain boundary region. The hybrid interface can hinder chemical oxidation at high-temperature depending on the carbon allotropy. As a result, the hybrid materials with CNT display high ionic conductivity and activation energy, reducing the space charge layer and charge distribution. This feature enhances the electromechanical properties at room temperature. We especially disclose electrostriction in the CNT-based hybrids superior to the pure CGO and follow a non-Newnham relation. Notably, integrating carbon materials with metal oxides using the SPS can generally be applied to synthesising a range of functional metal oxide composite.